2019
DOI: 10.1021/acs.inorgchem.9b02085
|View full text |Cite
|
Sign up to set email alerts
|

Cotemplating Assembly and Structural Variation of Three-Dimensional Open-Framework Sulfides

Abstract: Open-framework sulfides (H 3 O)-KCu 6 Ge 2 S 8 (1) and (H 3 O)RbCu 6 Ge 2 S 8 (2) were prepared by a cotemplating strategy. This shows that alkali-metal and protonated water cations act as cotemplates to direct the three-dimensional open-framework sulfides. These templates direct two types of onedimensional channels that arrange parallelly, and different types of templates reside in different types of channels. By introduction of the Cs cation into the synthetic systems of 1 and 2, (H 3 O)K 0.6 Cs 0.4 Cu 6 Ge … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 42 publications
2
9
0
Order By: Relevance
“…As mentioned above, in this study, we made a modification in the preparation process of 1 and used excess amount of sulfur powder in the reactants, while other reaction conditions, such as reaction time, temperature, solvent, and the molar ratios of Cu/GeO 2 /K 2 CO 3 , remained the same as those in the literature . The molar ratio of S/GeO 2 in the reactants was varied from 14.17 to 20.17 in a sequential manner, and the results showed that the amount of unknown impurity in the final product decreased with the increasing molar ratio of S/GeO 2 .…”
Section: Resultsmentioning
confidence: 95%
See 4 more Smart Citations
“…As mentioned above, in this study, we made a modification in the preparation process of 1 and used excess amount of sulfur powder in the reactants, while other reaction conditions, such as reaction time, temperature, solvent, and the molar ratios of Cu/GeO 2 /K 2 CO 3 , remained the same as those in the literature . The molar ratio of S/GeO 2 in the reactants was varied from 14.17 to 20.17 in a sequential manner, and the results showed that the amount of unknown impurity in the final product decreased with the increasing molar ratio of S/GeO 2 .…”
Section: Resultsmentioning
confidence: 95%
“…Although the crystal structure of 1 was previously reported in the literature, herein, it is briefly described for better understanding the conduction. Crystals of 1 belong to a tetragonal system with the space group P 4/ m .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations